2013
DOI: 10.1111/j.1728-4457.2013.00589.x
|View full text |Cite
|
Sign up to set email alerts
|

Surplus Chinese Men: Demographic Determinants of the Sex Ratio at Marriageable Ages in China

Abstract: We explore the demographic factors contributing to China's unbalanced sex ratio at marriagable ages. We develop a stable population model of the sex ratio at marriagable ages, and compare a series of population projections with alternative underlying assumptions about the key demographic inputs. The stable population model demonstrates that several demographic factors interact to influence the sex ratio at marriagable ages, including the sex ratio at birth, population growth, the age gap of marriage partners, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 28 publications
(32 reference statements)
0
18
0
Order By: Relevance
“…Due to the uncertain trend of future SRBs, some scholars have adopted multiple scenarios of SRBs in population projection (Guilmoto, 2012; Tucker and Van Hook, 2013). In this paper, our focus is not on the effect of different SRBs on the marriage market, so we employ just one SRB assumption as mentioned above.…”
Section: Projection and Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the uncertain trend of future SRBs, some scholars have adopted multiple scenarios of SRBs in population projection (Guilmoto, 2012; Tucker and Van Hook, 2013). In this paper, our focus is not on the effect of different SRBs on the marriage market, so we employ just one SRB assumption as mentioned above.…”
Section: Projection and Parametersmentioning
confidence: 99%
“…Even if the fertility rates were to remain constant, with different SRBs the total population’s age and sex structure will be quite different in the long term (Jiang et al, 2011b). Tucker and Van Hook (2013) employed different assumptions about SRBs, fertility levels, and spousal age gaps, and showed that these factors affected the marriage squeeze, but could not separate their effects.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, this transition will present numerous economic, social, and political challenges related to adequate care for the elderly and a shrinking workforce (see, for example, Li, Chen, and Jiang 2011;Zhang, Yang, and Wang 2011;Chen and Powell 2012). Similarly, the highly skewed sex ratio is perceived as a problem for social stability and the marriage market (Zhu, Lu, and Hesketh 2009;Tucker and Van Hook 2013).…”
Section: Studies In Family Planning 45(4)mentioning
confidence: 99%
“…Hence, the smaller size of younger birth cohorts exacerbates the effect of SRB imbalances on the marriage market (Guilmoto 2012; Cabré 1994, 1993). Whether they measure marriage market imbalances with sex-ratio indices (Tucker and Van Hook 2013; Rallu 2006; Attané 2005; Tuljapurkar et al 1995), cross-sectional indicators that weight sex ratios by age-specific marriage rates (Guilmoto 2012; Tuljapurkar et al 1995), or marriage simulations (Sharygin, Ebenstein and Das Gupta 2013; Tucker and Van Hook 2013; Guilmoto 2012), the verdict from these studies is clear – men will experience a rise in non-marriage due to a shortage of potential brides in the coming decades. Marriage markets however are not only structured by age and sex, but also by social factors such as education.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Most studies of the impact of skewed sex ratios at birth (SRB) on nuptiality have focused on the Chinese scenario (Tucker and Van Hook 2013; Sharygin, Ebenstein and Das Gupta 2013; Guilmoto 2012; Attané 2005; Jiang et al 2007; Tuljapurkar et al 1995) with few studies of the Indian scenario. Guilmoto 2012 is an exception.…”
mentioning
confidence: 99%